O desafio da tradução entre Língua Portuguesa e libras diante do fenômeno da sinonímia - ARAÚJO, Marília do Socorro Oliveira (2023)
The research is focused on the synonymy phenomenon in translation between the Portuguese language and Brazilian sign language (Libras), focused on the work of Libras professional interpreter. The objective is to analyze the synonymy in the Portuguese language and LIBRAS as well as verify the semantic value of the sentences translated by LIBRAS interpreter. The theoretical basis is formed by Lyons (1981); Fernandes & Correia (2011); Chomsky (2006) and de Saussure (2006), and studies of the Quadros (2004) and Rosa (2008). We use quantitative and qualitative approach. For data collection was assembled a glossary with words in Portuguese, used in sentences, which were submitted to translations by interpreters of Abaetetuba city. From translations analyzes were made presented in this work and it was concluded that the synonymy, as a constitutive process of translation, is essential to ensure the meaning in the target language. So any semantic loss as verified in the analyzes in translation with the literal meaning and information increase the interpreter translating for LIBRAS synonymic caused damage to the process. Consequently, the LIBRAS interpreter's work is very important for the deaf and the translation must be carried out with ethics and responsibility. To be a resource to help the understanding of the deaf in a language that he does not hear.